INTERPRETASI LAPISAN BATUAN BAWAH PERMUKAAN BERDASARKAN ANALISIS DATA GEOLISTRIK - Mukaddas, Abdul (MEKTEK, 2009)
The research aim is to procure lithology and depth rock that has water potentially contaned by using receptivity geolelectric of Shlumberger configuration. The project was conducted at the District of Beka which focused on 6 sample geoelectric points. Each point is restricted in the length area of 400 m. The geoelectric data processing was checked by available curve technique with helping inversion program. The processing based on responding of rock resistivity. Resistivity value of sand is between 3.5 and 11.5 Ohm-meter. Meaning that water potentially is available in the depth of around 40 m under land surface